ANALISIS BIAYA PRODUKSI PETERNAKAN AYAM PETELUR DI KABUPATEN TULUNGAGUNG (Studi Kasus di Dofir Layer Farm) - Zeni Budi Santoso; Eddy Trijana Sudjani; Adi Andaka (AVES: Jurnal Ilmu Peternakan, 2017)
This research was conducted at the lender Layer Farm owned by H. Dofir located in the village Rejotangan Rejotangan Tulungagung subdistrict. The aim was to determine the analysis of financial analysis in laying hens at the DLF Rejotangan Tulungagung subdistrict, It examines some of the financial aspects of the financial analysis used are, Net B/C Ratio, Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP) and Switchings Value. Based on the results of the calculation of financial feasibility of the business laying on Dofir Layer Farm then obtained when the initial conditions of business where there has been no increase productivity showed NPV greater than 0, namely Rp 2,359,608,260.73 IRR is greater than the discount rate that is equal to 71 percent, Net B/C of 3.28 is greater than one, PP is shorter than the life of the project is 2 years and 3 months. Business sensitivity analysis is feasible because decrease of production by 26 percent, the price increase of 28.6 percent DOC and feed prices rise by 37 percent NPV indicates value greater than zero, the Net B/C is greater than 1, IRR more greater than the discount rate and the PP before the age of the business end. In the conditions of development of the results obtained from the analysis showed that this business is financially feasible when done business development by improving the productivity of laying chickenKeyword : poultry, financial and business.